Towards understanding Lepidocyrtus Bourlet, 1839 (Collembola, Entomobryidae) II: new Australian species - Mateos, Eduardo; Greenslade, Penelope (Zootaxa, 2021)
The genus Lepidocyrtus Bourlet is currently considered to consist of eight subgenera of which Setogaster Salmon is one. Here we describe three new species in this subgenus, L. agricolus sp. nov., L. coorongensis sp. nov., and L. nashi sp. nov. It appears to be the most widespread and numerically dominant subgenus of Lepidocyrtus in Australia. The three new species live in different habitats and in different parts of the continent. It is assumed they are endemic species, one is likely to be a short range endemic. The characters and a list of species of the Lepidocyrtus praecisus-group, and an identification key for the Australian species of genus Lepidocyrtus are provided.